علاقة سمات الشخصية بالصحة النفسية لدى مربي التربية الخاصة - درقيش، فاطمة الزهرة, مصباحي، وردة (جامعة الوادي university of Eloued, 2020)
الملخص: هدفت الدراسة إلى الكشف عن طبيعة العلاقة بين السمات الشخصية بالصحة النفسية لدى مربي التربية الخاصة. وتتضمن إشكالية الدراسة ما يلي: هل توجد علاقة بين السمات الشخصية والصحة النفسية لدى مربي التربية الخاصة. وتتضمن الفرضية العامة ما يلي: توجد علاقة ارتباطية بين سمات الشخصية و الصحة النفسية لدى مربي التربية الخاصة. والمنهج المستخدم في الدراسة هو المنهج الوصفي الارتباطي الذي يقوم على كشف علاقة بين متغيرين هما: السمات الشخصية و الصحة النفسية لدى مربي التربية الخاصة, أما عينة الدراسة فقد تكونت من 30 مربي, تم اختيارهم بطريقة قصدية وقد طبق عليهم الاستبيانين هما: 1. مقياس السمات الشخصية الخمس الكبرى المتكون من 44 فقرة. 2. استبيان الصحة النفسية مكون من 89 فقرة. أما البيانات فقد عولجت باستخدام: باستخدام الرزمة الإحصائية للعلوم الاجتماعية spss نسخة 22. معامل الارتباط بيرسون للكشف عن وجود علاقة ارتباطية بين متغيرات للدراسة. وقد توصلت الدراسة إلى النتائج التالية: 1_ توجد علاقة بين سمة الانبساطية والصحة النفسية لدى مربي التربية الخاصة. 2_ لا توجد علاقة بين سمة الطيبة والصحة النفسية لدى مربي التربية الخاصة. 3_ لا توجد علاقة بين سمة حيوية الضمير والصحة النفسية لدى مربي التربية الخاصة. 4_ لا توجد علاقة بين سمة العصبية والصحة النفسية لدى مربي مراكز التربية الخاصة. 5_ لا توجد علاقة بين سمة الاندماج والصحة النفسية لدى مربي التربية الخاصة. الفرضية العامة: لا توجد علاقة بين سمات الشخصية والصحة النفسية لدى مربي التربية الخاصة. Résumé :فرنسية أو انجلزية The study aimed to reveal the nature of the relationship between personality traits and mental health among the educators of special education centers. The problematic of the study includes the following: Is there a relationship between personality traits and mental health for the educators of special education centers? The general assumption includes the following: There is a correlation between personality traits and mental health for educators of special education centers. The method used in the study is the descriptive co relational approach that is based on uncovering a relationship between two variables: the personality traits and the mental health of the breeders of the special education centers, while the study sample consisted of 30 educators, who were intentionally chosen and the two questionnaires were applied to them: 1. Scale of the five major personality traits, consisting of 44 items. 2. Mental health questionnaire consisting of 89 items. As for the data, they were treated using: Using the statistical package for social sciences spss version 22. Pearson correlation coefficient to reveal the existence of a correlation between the variables of the study. The study found the following results: 1_ There is a relationship between the trait of extraversion and mental health among the educators of special education centers. 2_ There is no relationship between the characteristic of kindness and mental health for the educators of the special education centers. 3_ There is no relationship between the vital feature of conscience and mental health for the educators of special education centers. 4_ There is no relationship between the nervous trait and mental health for the educators of the special education centers. 5_ There is no relationship between the integration trait and mental health for special education educators. General hypothesis: There is no relationship between personality traits and mental health for special education educators.
دراسة ميدانية ببعض مراكز ذوي الحاجات الخاصة لولاية الوادي
مذكرة ماستر في علوم التربية تخصص تربية خاصة
Keywords: سمات الشخصية، الصحة النفسية، مربي التربية الخاصة; Traits de personnalité, santé mentale, éducatrice spécialisée; Personality traits, mental health, special education educator